Virulence perspective genomic research unlocks the secrets of Rhizoctonia solani associated with banded sheath blight in Barnyard Millet (Echinochloa frumentacea) - Patro, T. S. S. K.; Palanna, K. B.; Jeevan, B.; Tatineni, Pallavi; Poonacha, T. Tharana; Khan, Farooq; Ramesh, G. V.; Nayak, Anusha M.; Praveen, Boda; Divya, M.; Anuradha, N.; Rani, Y. Sandhya; et al. (Frontiers in Plant Science, 2024)
Banded sheath blight (Bsb) disease, caused by Rhizoctonia solani, is an emerging problem in barnyard millet cultivation. One of the significant goals of pathogenomic research is to find genes that cause pathogenicity in the fungus. A virulence profiling-based approach was employed and six R. solani isolates were collected from various ecological zones of India. The morphology and virulence of all of the isolates varied significantly. The most virulent strain was designated as RAP2 and its genome has been sequenced, assembled, and annotated. The RAP2 genome is 43.63 megabases in size and comprises 10.95% repetitive DNA, within which 46% are retroeleme nts, 8% are DNA transposons, and 46% are unidentified DNA. The Gene Ontology (GO) annotation of RAP2 proteins revealed that "phosphorylation", "membrane", and "ATP binding" have the highest gene enrichment in the "biological process", "cellular component" and "molecular function" domains, respectively. The genome comprises a majority of secretory proteins in the pectin lyase fold/virulence factor superfamily, which break down plant cell wall polymers to extract saccharides. The RAP2 genome is comparable to R. solani, which infects maize and rice, but it diverges further from soybean in terms of nucleotide-level genetic similarity. Orthologous clustering of RAP2 protein sequences with maize, rice, and soybeans yields 5606 proteins shared across all genomes. GO analysis of 25 proteins specific to the RAP2 genome found enrichment in the ethylene response, which can cause spore germination and infection in host plants.Interestingly, a 28-bp deletion in the RAP2 strain's cutinase domain was discovered in the cutinase protein, which might be important in the infection process, perhaps rendering the enzyme inactive or allowing the pathogen to infect barnyard millet while avoiding host defence. This study sheds light on the genetic makeup of R. solani, allowing researchers to discover critical genes related with pathogenicity as well as potential targets for fungicide development.